ERO modeling of beryllium erosion by helium plasma in experiments at PISCES-B. (August 2017) - Borodin, D.; Nishijima, D.; Doerner, R.P.; Brezinsek, S.; Kreter, A.; Kirschner, A.; Romazanov, J.; Borodkina, I.; Eksaeva, A.; Marenkov, E.; Linsmeier, Ch.
Highlights: Be physical sputtering by He ions was characterized at PISCES-B independently by spectroscopy and mass loss and interpreted using the ERO modeling. The influence of plasma conditions (ne /Te scan) and negative target biasing (sputtering ion impact energy) was investigated. The shapes and ratios of BeI and BeII line intensity profiles were reproduced showing the feasibility of the model and ADAS'96 atomic data. Both spectroscopy and mass loss (though deviate by a factor of 2.5) indicate that Ecktein'2007 fit for YBe←He (Ein ) based on SDTrimSP code results (BCA) overestimates the yields significantly. Metastable population tracking helps to reproduce the singlet to triplet line ratios. Remarkably, the initial population was MS:GS = 0.33 independently on plasma conditions and target biasing. Abstract: The beryllium erosion by helium plasma irradiation is studied at the PISCES-B linear plasma device and interpreted using the accompanying simulations by the ERO code. The influence of plasma conditions and varying negative biasing of the Be plasma target on BeI and BeII absolute line intensities are reproduced in detail by the simulations. The synthetic axial line intensity shapes and line ratios match with experiment. This indicates that atomic data are quite accurate. The initial population state of quasi-metastable 3 P level in BeI is found to be MS:GS = 0.33:1 for all conditions. The yields determined by the modeling interpretation are compared to the SDTrimSP code simulations in the binary collision approximation.